EFFECT OF HEAT THERAPY ON PAIN SEVERITY AND DURATION OF LABOR IN PRIMIGRAVIDA WOMEN - F Behmanesh, (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: Pain is a common phenomenon and an inevitable part of process of childbirth. Effective control of labor pain like other acute pains is very important for health and society. The aim of this study was to determine the effect of heat therapy on pain severity and duration of labor in primigravida women. METHODS: In this clinical trial study, 64 low risk nulliparous women were randomly divided into two groups (heat therapy and routine care groups). The control group got routine cares in obstetrics ward and heat therapy group in addition to these cares used warm bag for the low back from cervix dilatation of 3-4 cm to the end of first stage of labor and for perinea at the second stage. The intensity of labor pain was determined by Mc Gill pain questionnaire and duration of labor was determined by digital clock. Data was analyzed with t-test and chi square and Mann Whitney test (p=0.05). FINDINGS: Mean of pain intensity in first stage of labor in heat therapy group was 8.1±1 and in control group was 8.9±1 and mean of pain intensity in second stage of labor in heat therapy group was 8.3±1.9 and in control group was 9.9±1.9 (p=0.01). Also, in heat therapy group duration of the first and third stages of labor decreased. Mean of duration of the first stage of labor in heat therapy group was 16.6±74 minutes and in routine care group was 219.8±5.6 minutes meanwhile mean of duration of the third stage of labor in heat therapy group was 7.3±2.4 minutes and in routine care group was 10.8±3.4 minutes (p<0.001) but duration of second stage of labor showed no significant difference between two groups. CONCLUSION: According to the results of this study, it seems that heat effects on the pain severity of first and second stages of labor and duration of the first and third stages of labor.